Sleep quality and fatigue in women with breast cancer during chemotherapy - Pamina Roberta da Silva; Lóris Aparecida Prado da Cruz; Talita Garcia do Nascimento; Thais de Oliveira Gozzo (Universidade Federal de Santa Maria, 2019)
Objective: To identify the occurrence of changes in sleep before, during and after chemotherapy treatment and to correlate sleep disorders with episodes of fatigue in women with breast cancer. Method: Twenty-six women followed at the Mastology Outpatient Clinic of a university hospital who responded to the Pittsburgh Sleep Quality Index and to the Functional Assessment of Cancer Therapy Fatigue to assess sleep and fatigue, respectively, in three moments. Results: The participants presented sleep disturbances throughout the treatment, characterized by night heat and difficulty to start sleep and that influenced the quality of sleep. There was a correlation between sleep quality and fatigue, with poor sleep quality increasing episodes of fatigue. Conclusion: Identifying the occurrence of these events during chemotherapy helps the professional team to provide guidelines for an adequate management of adverse events.